The Effect of Moringa Leaf Extract (Moringa Oliefera) On Triglyceride Levels in Streptozotocin Induced Type 2 Diabetes White Wistar Rats - Raya, Maxianus K; Vegasari, Novia; Nuburi, Dorci; Maryorita, Blestina; Rahayu, Endah Sri (Poltekkes Kemenkes Palu, 2023)
High blood sugar levels can hasten the liver's production of triglycerides. Normally, the body uses glucose as one of its energy sources. This study aimed to determine changes in the weight of mice and decrease triglyceride levels in mice by administering Moringa leaf extract. This type of research is a pure experiment with a